"Depression in Elderly People: a Non-Systematic Review" - Ana Henriques Pereira; Luísa Soares; Ana Lúcia Faria (Universidade Estadual de Alagoas, 2023)
An aging worldwide population, associated with more and more future dependence, demands scientific reflection on care for older adults. Frequently, and even admitted as desirable, such care is usually provided by an informal caregiver. Informal care refers to a type of unpaid care that requires a previous relationship between a caregiver and an older adult, at home. Its demanding's can lead to negative implications, such as stress in the informal caregiver, refered in the literature as the term overload/overwork. It is related to poor physical and mental health, and sometimes, cases of depression stand out. In this review, we emphasize the urgency of psychological intervention with informal caregivers of older adults, to allow them to experience greater well-being and health, minimizing stress and fostering their growth, underlining the importance of considering their individual needs. Adding to the evidence in the area is Gilbert's Compassion-Focused Therapy, which is concerned with the relief or prevention of the suffering of individuals, specifically highlighting the act of caring.